(untitled) (Journal of Patan Academy of Health Sciences, 2019)
Truncus arteriosus (TA) is an uncommon congenital cardiac anomaly of which type IV is considered a rare variant. Recognition is crucial for proper treatment planning. The prognosis without treatment is poor. Echocardiography alone may not be useful in evaluation. Computed tomography (CT) finding is complicated. We report an 18 months child with ventricular septal defect (VSD), diagnosed on echocardiography, and further review by CT showed VSD with descending thoracic aorta giving rise to the pulmonary arteries suggestive of pseudo truncus (Collet and Edwards Truncus arteriosus Type IV) and right sided aortic arch with mirror image branching.